Comparative genomics analysis of the multidrug-resistant Aeromonas hydrophila MX16A providing insights into antibiotic resistance genes - Guo, Yuxin; Zeng, Chenxi; Ma, Chenjie; Cai, Hongjiao; Jiang, Xinglong; Zhai, Shaowei; Xu, Xiaojin; Lin, Mao (Frontiers in Cellular and Infection Microbiology, 2022)
In this paper, the whole genome of the multidrug-resistant Aeromonas hydrophila MX16A was comprehensively analyzed and compared after sequencing by PacBio RS II. To shed light on the drug resistance mechanism of A. hydrophila MX16A, a Kirby-Bauer disk diffusion method was used to assess the phenotypic drug susceptibility. Importantly, resistance against β-lactam, sulfonamides, rifamycins, macrolides, tetracyclines and chloramphenicols was largely consistent with the prediction analysis results of drug resistance genes in the CARD database. The varied types of resistance genes identified from A. hydrophila MX16A revealed multiple resistance mechanisms, including enzyme inactivation, gene mutation and active effusion. The publicly available complete genomes of 35 Aeromonas hydrophila strains on NCBI, including MX16A, were downloaded for genomic comparison and analysis. The analysis of 33 genomes with ANI greater than 95% showed that the pan-genome consisted of 9556 genes, and the core genes converged to 3485 genes. In summary, the obtained results showed that A. hydrophila exhibited a great genomic diversity as well as diverse metabolic function and it is believed that frequent exchanges between strains lead to the horizontal transfer of drug resistance genes.